Evaluation of plantain genotypes for yield and other characters (Bangladesh Journal of Agricultural Research, 2018)
An experiment was carried out at the Regional Agricultural Research Station, BARI, Ishurdi, Pabna during 2013-15, with eleven genotypes of plantain to evaluate their performances for yield attributes, yield and quality characters. The genotypes included in this investigation were MP001, MP002, MP003, MP006, MP007, MP015, MP018, MP024, MP025, ISD002 and BARI Kola-2 as check. The experiment was laid out in randomized complete block design with three replications. The genotype MP002 produced the maximum number of fingers/bunch (105.67) closely followed by BARI Kola-2 (103.00) and MP015 (101.00). Both the genotypes MP024 and MP025 showed the highest fruit length (21.70 cm), but ISD002 gave the maximum fruit girth (16.78 cm), which was statistically similar with that of MP003 (16.30 cm) and MP024 (16.33 cm). The highest yield and the maximum number of hands were produced by the genotype MP024 (47.81 t/ha and (8.33/bunch) followed by MP015 (36.70 t/ha and 6.33/bunch). Fingers of the genotypes required boiling time in the range of 20.00 min (MP001) to 15.00 min (BARI Kola-2). Flesh of all genotypes possesses pleasant aroma except MP002, MP003 and ISD002. Among the eleven genotypes MP001, MP006, MP007, MP008, MP015 and MP024 were found better when cooked as smashed. The genotype ISD002 took the maximum time (467.33 days) to reach the edible maturity stage of fruits whereas MP024 required the minimum (339.00 days). The genotypes MP015 and MP024 performed better than BARI Kola-2 in respect of bunch weight, fruit size, productivity index, yield, sucker production and qualitative characters.Bangladesh J. Agril. Res. 43(1): 71-80, March 2018